Co oxidation: effect of Ce and Au addition on MnOx catalysts - Peluso, Miguel Andrés (2012)
The effect of cerium and/or gold addition to a manganese oxide which was greatly active in CO oxidation was studied. The catalysts obtained by this way were characterized by N2 adsorption, XRF, XRD and TPR, and their catalytic activity was measured in the CO oxidation reaction. The pure MnOx catalyst was active in the CO oxidation but the addition of 5 wt % cerium decreased their catalytic activity. Adding 2 wt % gold improved the activity of MnOx and Ce/MnOx and caused a slight decrease of the catalyst specific area and of the average oxidation state of manganese in catalysts, which was found between 3.3 and 3.6. The order of activity found on the basis of T50 for the four catalysts was: Au/MnOx > Au/Ce/MnOx > MnOx > Ce/MnOx, with T50 of 89, 95, 99 and 139 °C, respectively. The solids Au/MnOx and Au/Ce/MnOx presented a T10 of 30 and 49 °C, indicating that gold favored the conversion at room temperature. The effect of water vapor on the reaction was also analyzed, finding a decrease in the catalytic activity of all catalysts, due to the blocking of active sites in the catalyst surface.